A Numerical Approach to Analyze Detail Mechanical Characteristic at the Crack Tip of SCC in Dissimilar Metal Welded Joints - He Xue; Yuman Sun; Shun Zhang; Rehmat Bashir; Youjun Zhao; Hongliang Yang; Shuai Wang; Yongjie Yang (Advances in Materials Science and Engineering)
The mechanical characteristic at the crack tip is one of the main factors affecting the stress corrosion cracking (SCC) in dissimilar metal welded joints (DMWJs). In this research, to evaluate the effect of heterogeneous material properties on the mechanical characteristic at the crack tip of DMWJs accurately, a heterogeneous material model of the SA508 Cl.3-Alloy 52M DMWJ was established based on USDFLD subroutine in ABAQUS. The comparison of the traditional “Sandwich” material model with the heterogeneous material properties, stress-strain conditions, and the plastic zone around the crack tip at the interference zone has been analyzed by the finite element method (FEM). The results indicated that the heterogeneous material model could characterize the mechanical properties of the SA508 Cl.3-Alloy 52M DMWJs accurately. In addition, the crack at the interface zone between materials will deflect along with the weld metal in two material models.